2012
DOI: 10.1186/cc11401
|View full text |Cite
|
Sign up to set email alerts
|

The top cited clinical research articles on sepsis: a bibliometric analysis

Abstract: IntroductionThe objective of this study was to identify and characterize the most highly cited clinical research articles published on sepsis.MethodsA comprehensive list of citation classics in sepsis was generated by searching the database of Web of Science-Expanded (1970 to present) using keywords 'sepsis' or 'septic shock'. The top 50 cited clinical research papers were retrieved by reading the abstract or full text if needed. Each eligible article was reviewed for basic information, including country of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 17 publications
5
36
0
1
Order By: Relevance
“…Browsing through the top-100 list shows that most articles fall into two subject areas, degenerative disease and sports traumatology; correspondingly, individuals who were first or last authors of multiple articles in the list also commonly showed a focus on one of these two areas. The leading country of origin was the U.S., similar to the case in other medical fields (e.g., general surgery 1 , general orthopaedics 5 , urology 14 , critical care medicine 15 , emergency medicine 16 , and sepsis research 17 ). This is likely a consequence of the U.S. population size and research budgets.…”
Section: Discussionmentioning
confidence: 99%
“…Browsing through the top-100 list shows that most articles fall into two subject areas, degenerative disease and sports traumatology; correspondingly, individuals who were first or last authors of multiple articles in the list also commonly showed a focus on one of these two areas. The leading country of origin was the U.S., similar to the case in other medical fields (e.g., general surgery 1 , general orthopaedics 5 , urology 14 , critical care medicine 15 , emergency medicine 16 , and sepsis research 17 ). This is likely a consequence of the U.S. population size and research budgets.…”
Section: Discussionmentioning
confidence: 99%
“…The bibliometric studies can help to (I) identify hotspots in a certain area; (II) network connections between subspecialties; (III) the leading investigators; and (IV) author's scientific output. Many bibliometric studies focused on a few vital issues in the field of CCM such as sepsis, severe brain injury and acute kidney injury (6)(7)(8). However, to the best of our knowledge, there is no bibliometric study that analyzes the entire CCM area.…”
Section: Introductionmentioning
confidence: 99%
“…The bibliometric analyses in other areas also showed that the United States ranked high on the list (13,14). These findings clearly show that the United States is at the forefront of studies on breast cancer.…”
Section: Discussionmentioning
confidence: 50%